Relation between pelvic organ prolapse and menopausal hormone therapy: nationwide cohort study - Hee-Yeong Jung; Tae-Ran Kim; Gwan Hee Han; Jin-Sung Yuk (Obstetrics & Gynecology Science)
Objective To analyze the relationship between pelvic organ prolapse (POP) and menopausal hormone therapy (MHT). Methods This retrospective cohort study used Korean National Health checkup and insurance data from 2002 to 2019. Women who used MHT for more than 6 months between 2002 and 2011 were included in the MHT group; postmenopausal women with no MHT use comprised the non-MHT group. Results In the non-MHT group, there were 1,001,350 women, while the MHT group had 353,206 women. Tibolone (adjusted hazard ratio [aHR], 0.87; 99% confidence interval [CI], 0.818-0.926) and combined estrogen plus progestin by the manufacturer (CEPM) (aHR, 0.821; 99% CI, 0.758-0.89) were associated with reduced POP risk. The other oral MHT groups and the transdermal estrogen group showed no significant difference in POP risk compared with the non-MHT group (other oral MHT: aHR, 1.045; 99% CI, 0.941-1.161) (transdermal estrogen: aHR, 1.252; 99% CI, 0.731-2.145). Lower body mass index (BMI) (<18.5) was associated with reduced POP risk (aHR, 0.822; 99% CI, 0.698-0.968), while a BMI between 23 and 29.9 was associated with increased risk (BMI 23-24.9: aHR, 1.143; 99% CI, 1.088-1.2) (BMI 25-29.9: aHR, 1.173; 99% CI, 1.12-1.228). All parities had a higher POP risk than parity 1 (parity 0 or no response: aHR, 1.785; 99% CI, 1.589-2.005; parity 2: aHR, 1.434; 99% CI, 1.292-1.592; parity ≥3: aHR, 1.916; 99% CI, 1.712-2.144). Conclusion Tibolone and CEPM use were associated with reduced POP risk in postmenopausal women. Other MHT types showed no significant association with POP.